Exploring the transition from preventive maintenance to predictive maintenance within ERP systems by utilising digital twins - Damant, Liam; Forsyth, Amy; Farcas, Ramona; Voigtländer, Melvin; Singh, Sumit; Fan, Ip-Shing; Shehab, Essam (IOS Press, 2021)
Over the years, there has been an advancement in how manufacturing companies conduct maintenance. They have begun transitioning from Preventive Maintenance (PM) to Predictive Maintenance (PdM). With the introduction of technologies such as Digital Twin (DT), Internet of Things (IoT), and Intelligent Manufacturing (IM), the world is rapidly changing, thus allowing companies to optimise existing processes, products and reduce costs. The existing literature offers limited investigations and best practices in the end-to-end optimisation for maintenance transformation. The current paper intends to explore (a) the transition from PM to PdM and (b) the utilisation of DTs and IM for maintenance optimisation. The paper articulates the scope and features of end-to-end maintenance optimisation for asset uptime and cost benefits. The findings can help industries understand the introductions and advancements of technologies for predictive maintenance and end-to-end optimisation with the benefit of investigating and illustrating how companies can move forward.
Keywords: Predictive Maintenance; Preventive Maintenance; Digital Twin; Internet of Things; Enterprise Resource Planning (ERP); Artificial Intelligence; Intelligent Manufacturing; Optimisation; Transdisciplinary